Discovery Learning Sebagai Teori Belajar Populer Lanjutan: Array - Heri Febri Yadi Yadi; Neviyarni; Herman Nirwana (Citra Dharma Cindekia, 2022)
The learning model is a framework that provides a systematic description for carrying out learning in order to help students learn in a certain way to achieve. That is, the learning model is a plan or a pattern that is used as a guide in planning classroom learning or learning in tutorials. Discovery Learning is a learning method that applies Inquiry-Based Instruction. Discovery Learning is learning that encourages students to investigate on their own, discover and build on past experiences and knowledge, use intuition, imagination, and creativity, and seek new information to find new facts, correlations, and truths. Learning is not the same as absorbing what is said or read, but actively learning to find answers and solutions yourself. Discovery Learning is one of the learning methods known to improve the quality of education in learning in advanced theory.